Bioactive Composition and Antioxidant Characteristics of Calophyllum inophyllum Seed Flour: Potential Relevance for Functional Food Development - Azizul Berlyansah; Andreanyta Meliala; Paramita Narwidina; Wira Mondana; Beatrice Cynthia Walter (Window of Health : Jurnal Kesehatan, 2026)
Metabolic diseases such as obesity, type 2 diabetes mellitus, and dyslipidemia are health challenges, with over one billion people affected by obesity and 589 million adults living with diabetes. This study evaluated the antioxidant activity, anthocyanin content, amino acid profile, proximate composition, and fatty acid (FFA) profile of Calophyllum inophyllum seed flour as a functional food ingredient. Seeds were collected from the Batam Botanical Garden, Indonesia, and processed by freeze-drying. Antioxidant activity was determined using the DPPH assay (IC₅₀), anthocyanin content was measured spectrophotometrically, and proximate composition, amino acid profile, and FFA composition were analyzed using standardized methods, including GC-FID. All analyses were performed in triplicate (n = 3), and results were expressed as mean ± standard deviation. The flour was predominantly composed of lipids (65.26 ± 0.13%), followed by carbohydrates (21.92 ± 0.10%) and proteins (8.39 ± 0.02%), with low moisture content (2.64 ± 0.03%). The DPPH assay yielded an IC₅₀ value of 13,362.04 ± 1.70 mg/L, indicating limited free radical scavenging activity, while anthocyanins were not detected. The amino acid profile was characterized by high glutamic acid content and the presence of essential amino acids, including leucine, valine, and lysine. The fatty acid profile was dominated by unsaturated fatty acids, particularly oleic and linoleic acids. These findings indicate that Calophyllum inophyllum seed flour contains nutritionally relevant amino acids and unsaturated fatty acids, supporting its potential relevance for functional food development. Further studies are required to characterize additional bioactive compounds and evaluate their biological activities in vivo.